Narrator and Narrative Vision in the Poetry of Nizar Qabbani (Journal of Hama University, 2020)
Narration accounted for modern literary studies at the beginning of the twentieth century, as critics focused on using narration studies in poems with fictional structures, and our research dealt with the narrator study - as an essential pillar of the structural building of the narration - and the narrative vision also in the first part of Nizar Qabbani's poetic works. The poems of this kind narrative are abundant in poetry.This study included a briefing on the concept of the narrator, and its manifestation of its two types (theater and non-theater) in the poetry of Nizar Qabbani through theoretical and applied perspectives, and the projection of the narrator's character through narrative vision, and identify types in narrative work, and highlight its role in clarifying the narrator's personality, as the first controller in Presenting a world of his story, and the only medium between him and the recipient.